Structurally-controlled failure and damage around an opening in faulted Opalinus Clay shale at the Mont Terri Rock Laboratory: In-situ experimental observation and 3D numerical simulation - Zhao, Chenxi; Lei, Qinghua; Ziegler, Martin; Loew, Simon (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2024)
We present a combined experimental and numerical study of failure and damage in faulted Opalinus Clay shale around an opening at the Mont Terri Rock Laboratory, Switzerland. An experiment borehole with a diameter of 0.6 m and a length of 12.9 m intersecting a major fault zone at an acute angle of ∼40° was drilled, with subsequent overbreaks closely monitored. To investigate the underlying mechanisms that lead to the observed overbreaks, we developed a 3D geomechanics model to simulate the deformation and failure behaviour of faulted Opalinus Clay shale. To represent geological structures including the major fault zone and secondary fracture sets, a site-specific fracture network was constructed. Our model captured many important geomechanical properties and responses of the faulted Opalinus Clay shale, such as anisotropy of the shale matrix, deformation of the fault zone, dislocation of secondary fractures, and growth of new cracks as well as generation of overbreaks around the opening. We compared our simulation results with in-situ experimental observation of short-term overbreak patterns along the borehole and found that the overbreak occurrence is strongly controlled by both stress conditions and geological structures. Our results indicate that the damaged zone is characterised by an inner shell and an outer shell, where the former (dominated by extensive tensile/shear cracks) has a thickness of about one quarter of the borehole diameter and the latter (dominated by sparse shear cracks) extends by half to one borehole diameter into the surrounding rock. We further elucidated the impacts of the major fault zone and secondary fracture sets as well as the borehole–fault intersection angle on the deformation, damage, and failure characteristics. The findings and insights obtained in this study have important implications for the stability evaluation of waste emplacement drifts and long-term safety assessments of nuclear waste galleries in faulted argillaceous rocks. •3D simulation captures overbreak and damage of Opalinus Clay around an opening.•Interplay of stress and heterogeneity drives overbreak formation and pattern.•Damaged zone of a two-shell structure rotates with the distance to a fault zone.•Acute angled faults exert strong controls on overbreak and damage generation.